A Corpus-based study on collocations of keywords in English business articles about the European debt crisis. M.A Thesis Linguistics: 60 22 15 - Đào, Thị Ngọc Nguyên (University of Languages and International Studies, 2017)
One of the most problematic areas when vocabulary is dealt with is collocation. It is often seen as arbitrary and overwhelming, a seemingly insurmountable obstacle to the attainment of native like fluency. This piece of work presents a study on collocation (...)